Demographic characteristics of population of Slovenian cities in the first decade of 21st century - Kelc, Stanko (Journal for Geography, 2012)
We analyzed available statistical data to establish present demographic characteristics of the population of Slovenian cities and their recent changes. According to the statistical definition of cities the share of urban population in Slovenia represents half of its total population. The number of population in Slovenian cities is generally decreasing or stagnating, the coefficient of masculinity was growing in the last decade, but not much more than in Slovenia in general, the ageing of population was also a bit faster in urban areas and their ageing index is considerably higher than the Slovenian average. Urban areas also had a considerably larger share of immigrants from abroad in comparison with the national average while employed and unemployed persons were relatively equally distributed among urban and other areas. The level of education was considerably above the national average. We also compared natural growth data which showed that urban areas in 2002 experienced the decrease that was below national average and the increase in 2011 that was also lower than in Slovenia in general.
Keywords: slovenian cities; demography